“In truth, I was really a pioneer”: Female Entrepreneurship and Selfhood Formation in Bethlehem's Diasporic Merchant Community, 1900–1940 - Eibhlin Priestley (Mashriq & Mahjar)
This article explores girlhood, marriage, and female entrepreneurship in Bethlehem’s diasporic merchant families in the early twentieth century, focusing on the lives of two women whose transition from girlhood to womanhood overlapped with their diasporic experiences in the Americas. Focusing on oral history interviews with Katrina Sa’ade and the memoir of Victoria Kattán de Hirmas, this study examines the outward expansion of Bethlehem’s merchant middle-class from the perspective of women whose lives were indelibly shaped by these ventures. This piece argues that transnational migration and marriage equipped women with essential skills for commercial success and highlights their self-perception as pioneers who forged new paths in the mahjar. Flexible roles for women in Bethlehem’s merchant community, underpinned by Ottoman cultural transformations and the innovative and outward-looking values which underpinned the community’s bold business enterprises, also played a significant role in fostering female entrepreneurship. By tracing the journeys and entrepreneurial endeavors of Katrina and Victoria, the study underscores the transformative impact of migration on understandings of womanhood, work, and identity within diasporic communities, and emphasizes the agency and resilience of women who redefined possibilities for Palestinian women in the diaspora.